Antibody–drug conjugates treatment of small cell lung cancer: advances in clinical research - Yuan Meng; Xuerui Wang; Jie Yang; Meiying Zhu; Minghui Yu; Longhui Li; Yangyueying Liang; Fanming Kong (Discover Oncology, 2024)
Abstract Small cell lung cancer (SCLC) is an extremely aggressive cancer with a relatively low median survival rate after diagnosis. Treatment options such as chemotherapy or combination immunotherapy have shown clinical benefits, but resistance and relapse can occur. Antibody–drug conjugates (ADCs), as a novel class of biopharmaceutical compounds, have broad application prospects in the treatment of SCLC. ADCs consist of monoclonal antibodies that specifically target cancer cells and are attached to cytotoxic drugs, allowing for targeted killing of cancer cells while sparing healthy tissues. Current clinical studies focus on Delta-like protein 3 (DLL3), CD56, Trophoblast cell surface antigen 2 (Trop-2), B7-H3, and SEZ6. Although toxicities exceeding expectations have been observed with Rova-T, drugs targeting TROP-2 (Sacituzumab Govitecan), B7-H3 (DS-7300), and SEZ6 (ABBV-011) have shown exciting clinical benefits. In this review, we collect the latest clinical evidence to describe the therapeutic efficacy and safety of ADCs in SCLC and discuss prospects and challenges.